Contribución al estudio palinológico del género Helianthemum Miller (Cistaceae) en el sureste peninsular - Roman, Jose? M.; Blanca, Gabriel; Di?az de la Guardia, Consuelo; Romero, Ana T. (Acta Botanica Malacitana, 1992)
.